Field Straw Management – A Techno Economic Perspectives - Mangaraj, S.; Kulkarni, S. D. (Journal of the Institute of Engineering, 2011)
The study was conducted in the combine harvested paddy (variety-Kranti) and wheat (HI-8498) field. The crop gatherer cum baler was used for collection and baling of crop residues left in the field. Collection and gathering losses were determined for given condition and quantity of straw in the field. Moisture content of loose paddy and wheat straw was 15% and 8% respectively. Field operation was conducted at forward speed of 2.7 km/h and with collecting width of 1240 mm. The number of twine tied bales obtained per h was 181 and 87 with bale density of 200 and 102 kg/m3 and bale mass of 22 and 10 kg respectively for rice and wheat crop. The collection and gathering losses were 18.40% for rice and 41.12 % for wheat. The cost of producing one twine tied bale was Rs.2.75 and Rs.5.00 for rice and wheat respectively. At nominal price of rice straw (Rs. 0.25/kg) and wheat straw (Rs. 0.75/kg) the net income from straw collection and baling using the machine was Rs. 607.00 per ha and Rs. 235.00 per ha for rice straw and wheat straw respectively. Straw management in the combine harvested fields by straw collection and baling in the field is considered as an appropriate and economically viable option for timely use of the field for subsequent sowing. Key words: Straw management; Techno economic DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5107 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 153-159 Uploaded Date: 20 July, 2011